Polarization Effect of a PMT-like Avalanche Photodiode Based on GaN/AlN Periodic Stack Structure - Li, Qian; Chen, Feiliang; Li, Mo; Kang, Jianbin; Wang, Wangping; Jian, Zhang (2018 International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD), 2018)
APD based on AlN/GaN periodically stacked structure (PSS) has been proposed to obtain a high ionization coefficient ratio of more than 100 and a record high linear-mode gain of 10 4 . Here the full p-i-p-i-n SAM structure of the PSS APD is simulated to discuss the influence of the polarization effect which cannot be ignored. The dependence of the device performances on polarization effect and structure parameters in the PSS APD is studied in detail, which will be helpful for the design and optimization of PSS APD.